BIOMASS AND CARBON DIOXIDE CAPTURE: RESEARCH FOR Araucaria angustifolia (Bertol.) Kuntz - Favarin, José Augusto Spiazzi; Guaraná Araújo, Emmanoella; Pinheiro Ferreira, Matheus; North Broadbent, Eben; Dalla Corte, Ana Paula (Biofix Scientific Journal, 2023)
Endangered species play an important role in studies on the quantification of biomass and carbon since, as their cutting is prohibited by law, they accumulate an essential stock in the forest. Thus, this work aimed to bring a scenario of the research being carried out with this theme with Araucaria angustifolia and other species of the same genus. To this end, bibliometric analysis was used, searching for published and indexed works in the Scopus, Web of Science, and Science Direct databases until 2021. We found 38 publications in 30 different journals, accumulating 72.5% of publications from the year 2014. Brazil was the country that produced the most research and also that received the most encouragement from research funding agencies. Biomass and carbon were the objects of most works, totaling 21. The direct method of quantification was the most used in 28 studies. Other methods were fitted models and simulation, muffle, dry combustion, wet combustion, and conversion factor methods to quantify carbon. The non-use of artificial intelligence was considered a gap in the research. Moreover, the little use of remote sensing, combined with artificial intelligence, should offer new methods for estimating biomass and carbon.